Membaca Pikiran Konsumen: Menyelami Psikologi di Balik Strategi Pemasaran yang Sukses - Putra, Halim Dwi Putra (BISMA : Business and Management Journal, 2025)
In this era of rapid globalization and digitalization, understanding consumer behavior is crucial for designing effective marketing strategies. Despite extensive research on consumer behavior, there remains a gap in the deep understanding of the psychology underlying consumer purchasing decisions. This study aims to explore how psychological elements influence successful marketing strategies, focusing on motivational factors, perception, and social influence. The method employed is a qualitative approach through in-depth interviews and content analysis of successful marketing campaigns. The qualitative approach allows researchers to gain a comprehensive understanding of how successful marketing campaigns are planned, implemented, and evaluated. In-depth interviews provide valuable insights from key players in these campaigns, such as marketing managers, advertising employees, and involved consumers. Additionally, content analysis offers profound insights into the messages conveyed in successful marketing campaigns. For example, by analyzing advertisements, brochures, and other promotional materials, researchers can identify patterns of effective communication and marketing strategies that successfully capture consumer attention. In this study, researchers can simulate successful marketing campaigns using data from interviews and content analysis, thereby identifying key factors that contribute to their success. This can serve as a reference for other companies in designing effective marketing strategies. Overall, the qualitative approach with in-depth interviews and content analysis is a powerful method for uncovering the keys to successful marketing campaigns. By delving deeply and analyzing content meticulously, researchers can obtain valuable insights for the marketing world. The study results show that a better understanding of consumer psychology, such as the use of emotions in advertising and tailoring products to consumer values, can enhance the effectiveness of marketing strategies. The theoretical contribution of this study is the development of a model that links consumer psychology to marketing decisions. Managerially, these findings provide useful insights for marketing practitioners to design more targeted and relevant strategies that better meet consumer needs.